Discover the best answers at Westonci.ca, where experts share their insights and knowledge with you. Our platform provides a seamless experience for finding reliable answers from a knowledgeable network of professionals. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform.
Sagot :
To determine the formula for the nth term of the quadratic sequence 2, 10, 22, 38..., we need to follow these steps:
1. Recognize the form of a quadratic sequence:
A quadratic sequence can be generally represented as:
[tex]\[ T_n = an^2 + bn + c \][/tex]
where [tex]\( T_n \)[/tex] is the nth term, and [tex]\( a, b, \)[/tex] and [tex]\( c \)[/tex] are constants that we need to determine.
2. Set up equations using known terms of the sequence:
For the given sequence, we can establish equations based on the first few terms.
- When [tex]\( n = 1 \)[/tex]:
[tex]\[ a(1)^2 + b(1) + c = 2 \implies a + b + c = 2 \][/tex]
- When [tex]\( n = 2 \)[/tex]:
[tex]\[ a(2)^2 + b(2) + c = 10 \implies 4a + 2b + c = 10 \][/tex]
- When [tex]\( n = 3 \)[/tex]:
[tex]\[ a(3)^2 + b(3) + c = 22 \implies 9a + 3b + c = 22 \][/tex]
3. Solve the system of equations:
We now have a system of three equations:
[tex]\[ \begin{cases} a + b + c = 2 \\ 4a + 2b + c = 10 \\ 9a + 3b + c = 22 \end{cases} \][/tex]
4. Find the values of [tex]\( a, b, \)[/tex] and [tex]\( c \)[/tex]:
Solving these equations, we get:
[tex]\[ a = 2, \quad b = 2, \quad and \quad c = -2 \][/tex]
5. Formulate the nth term:
Substituting [tex]\( a \)[/tex], [tex]\( b \)[/tex], and [tex]\( c \)[/tex] back into the general form:
[tex]\[ T_n = 2n^2 + 2n - 2 \][/tex]
Thus, the formula for the nth term of the given quadratic sequence is:
[tex]\[ T_n = 2n^2 + 2n - 2 \][/tex]
1. Recognize the form of a quadratic sequence:
A quadratic sequence can be generally represented as:
[tex]\[ T_n = an^2 + bn + c \][/tex]
where [tex]\( T_n \)[/tex] is the nth term, and [tex]\( a, b, \)[/tex] and [tex]\( c \)[/tex] are constants that we need to determine.
2. Set up equations using known terms of the sequence:
For the given sequence, we can establish equations based on the first few terms.
- When [tex]\( n = 1 \)[/tex]:
[tex]\[ a(1)^2 + b(1) + c = 2 \implies a + b + c = 2 \][/tex]
- When [tex]\( n = 2 \)[/tex]:
[tex]\[ a(2)^2 + b(2) + c = 10 \implies 4a + 2b + c = 10 \][/tex]
- When [tex]\( n = 3 \)[/tex]:
[tex]\[ a(3)^2 + b(3) + c = 22 \implies 9a + 3b + c = 22 \][/tex]
3. Solve the system of equations:
We now have a system of three equations:
[tex]\[ \begin{cases} a + b + c = 2 \\ 4a + 2b + c = 10 \\ 9a + 3b + c = 22 \end{cases} \][/tex]
4. Find the values of [tex]\( a, b, \)[/tex] and [tex]\( c \)[/tex]:
Solving these equations, we get:
[tex]\[ a = 2, \quad b = 2, \quad and \quad c = -2 \][/tex]
5. Formulate the nth term:
Substituting [tex]\( a \)[/tex], [tex]\( b \)[/tex], and [tex]\( c \)[/tex] back into the general form:
[tex]\[ T_n = 2n^2 + 2n - 2 \][/tex]
Thus, the formula for the nth term of the given quadratic sequence is:
[tex]\[ T_n = 2n^2 + 2n - 2 \][/tex]
Thank you for your visit. We are dedicated to helping you find the information you need, whenever you need it. We hope this was helpful. Please come back whenever you need more information or answers to your queries. Keep exploring Westonci.ca for more insightful answers to your questions. We're here to help.